Thermoplastic resin composite material with excellent mechanical property and preparation method thereof
By synthesizing modified diaphragm fibers and combining them with thermoplastic resins, the problem of insufficient mechanical properties of existing thermoplastic resin composites is solved, and the tensile strength and punching strength of the material are significantly improved, which is suitable for the automotive and aviation industries.
Patent Information
- Application Number
- CN202310950739.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
Existing thermoplastic resin composites have shortcomings in terms of mechanical properties, especially in terms of high strength, high stiffness and impact resistance, which have not fully met the needs of the automotive and aviation industries.
A new thermoplastic resin composite material is formed by synthesizing modified diaphragm fibers and combining them with thermoplastic resins. Modified diaphragm fibers improve their interface compatibility and mechanical properties with thermoplastic resins by polyglycidyl methacrylate coating and dithio group modification.
It significantly improves the mechanical properties of thermoplastic resin composites, including the improvement of tensile strength and punching strength. Usually, the tensile strength is increased by 10-22%, and the punching strength is increased by more than 60%, which meets the material performance of the automobile and aviation industries. Require.
Smart Images

Figure BDA0004368256720000071 
Figure BDA0004368256720000091 
Figure BDA0004368256720000111
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a thermoplastic resin composite material with excellent mechanical properties and a preparation method thereof. Background Art
[0002] Thermoplastic resin is a widely used polymer polyester resin. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance, excellent dimensional stability, etc. However, in some specific application fields, the mechanical properties of thermoplastic resin are very high, which limits the application of thermoplastic resin composite materials in some specific fields. For example, in the automotive and aviation industries, high strength, high stiffness and good impact resistance are required to meet the safety and structural performance requirements of automotive parts and aerospace devices.
[0003] At present, the strength, stiffness and impact resistance of thermoplastic resins are mainly improved by adding fiber reinforcements, such as glass fiber, carbon fiber, or particle fillers, such as glass beads, graphite, etc. However, the dispersion and uneven distribution of added fiber reinforcements and particle fillers may cause differences in the mechanical properties of the material in different directions, which may affect the overall performance and reliability of the product. In addition, the compatibility between them and thermoplastic resins is poor, resulting in the mechanical properties of the material failing to meet the requirements.
[0004] In view of these deficiencies, the present invention innovatively synthesizes a thermoplastic resin composite material with excellent mechanical properties, which has good mechanical properties. This thermoplastic resin composite material has not been reported so far, which has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention
[0005] In view of this, the present invention innovatively synthesizes a thermoplastic resin composite material with excellent mechanical properties, which has good mechanical properties and solves the technical problem of limited mechanical properties of thermoplastic resins in the prior art.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A thermoplastic resin composite material with excellent mechanical properties, which consists of the following components in parts by weight:
[0008] Thermoplastic resin 90-110 parts
[0009] Modified diabase fiber 10-16 parts
[0010] Antioxidant 0.1-0.5 parts
[0011] The modified diabase fiber is dithiol-modified diabase fiber coated with poly(glycidyl methacrylate).
[0012] In a further embodiment, the modified diabase fiber comprises the following steps:
[0013] (1) adding sodium dithiosulfide succinate, ethanol and diabase fiber into deionized water and stirring for reaction; then filtering, washing and drying to obtain dithiosulfide-modified diabase fiber;
[0014] (2) adding dithiol-modified diabase fiber, glycidyl methacrylate, an initiator, and a surfactant into deionized water for reaction, filtering, washing, and drying to obtain poly(glycidyl methacrylate)-coated dithiol-modified diabase fiber.
[0015] Preferably, the mass ratio of sodium dimercaptosuccinate, ethanol and diabase fiber in step (1) is (16-20): (50-60): (30-40).
[0016] The stirring reaction is carried out at a temperature of 40-60° C. and for a time of 8-12 hours.
[0017] Preferably, the mass ratio of the dithiol-modified diabase fiber, glycidyl methacrylate, initiator, and surfactant in step (2) is (30-40): (10-16): (0.1-0.3): (0.2-0.4).
[0018] The initiator is ammonium persulfate, sodium persulfate, potassium persulfate or diisopropyl peroxydicarbonate.
[0019] The surfactant is sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate or nonylphenol polyoxyethylene ether.
[0020] The reaction temperature is 30-40°C and the reaction time is 12-16h.
[0021] The antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite (Irganox168 for short), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (Irganox1010 for short) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (Irganox1330 for short) produced by BASF.
[0022] The thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyamide 6 (PA6).
[0023] The second object of the present invention is to provide a method for preparing the above-mentioned thermoplastic resin composite material, which comprises the following steps:
[0024] (1) Weigh 90-110 parts of thermoplastic resin, 10-16 parts of modified diabase fiber, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture;
[0025] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The modified diabase fiber in the present invention has a dithiol-modified diabase fiber on its surface, which can chemically bond with PGMA with anionic charge (epoxy group), so that the combination of PGMA and diabase fiber is tighter, so that PGMA can be evenly coated on the surface of the diabase fiber, and finally a new type of modified diabase fiber is prepared.
[0028] (2) PGMA in the modified diabase fiber can improve the interfacial compatibility between the diabase fiber and the thermoplastic resin due to the epoxy group, enhance the interfacial interaction between the two, and promote the mechanical properties of the thermoplastic resin.
[0029] (3) The mechanical properties of the thermoplastic resin composite material prepared by the present invention are greatly improved, and are significantly higher than the mechanical properties of the thermoplastic resin directly modified by diabase fiber. Generally, the tensile strength can be increased by 10-22%, and the punching strength can be increased by more than 60%. Therefore, it can be used in the field of automotive and household appliance materials and has excellent application prospects. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] The raw materials used in the following examples are as follows:
[0033] PBT (model 2002U), Polyplastics, Japan;
[0034] PP (model Z30S), Maoming Petrochemical;
[0035] PE (model 5070), Panjin ethylene;
[0036] PA6 (model CM1017), Toray, Japan;
[0037] PET (model 008L), Aclo, Canada;
[0038] Glycidyl methacrylate, Jinan Mingwei Chemical Co., Ltd.;
[0039] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;
[0040] Ammonium persulfate, Shandong Chuangying Chemical Co., Ltd.;
[0041] Diabase fiber, Guangxi Tonghai Diabase Mining Development Co., Ltd.;
[0042] Sodium dimercaptosuccinate, Shanghai Jixiang Biotechnology Co., Ltd.;
[0043] Ethanol, Shandong Taixi Chemical Co., Ltd.;
[0044] Sodium dodecylbenzenesulfonate, Jinan Aosili Chemical Co., Ltd.;
[0045] Antioxidant (model Irganox168, Irganox1010, Irganox1330), BASF.
[0046] Preparation Example 1
[0047] (1) Weigh 160 g of sodium dithiosuccinate, 500 g of ethanol, 300 g of diabase fiber, and 900 g of deionized water, add them into a reaction vessel, and stir at 40° C. for 8 h to obtain solution A;
[0048] (2) Filtering solution A, washing it, and drying it in a vacuum oven at 60° C. for 3 h to obtain dithiol-modified diabase fiber B;
[0049] (3) Weigh 300 g of dithiol-modified diabase fiber B, 100 g of glycidyl methacrylate, 1 g of initiator ammonium persulfate, 2 g of surfactant sodium dodecylbenzene sulfonate, and 700 g of deionized water, place them in a reaction vessel, react at 30° C. for 12 h, filter, wash, and dry to obtain modified diabase fiber M1 coated with polyglycidyl methacrylate.
[0050] Example 1
[0051] (1) Weigh 90 parts of PP, 10 parts of modified diabase fiber M1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;
[0052] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.
[0053] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0054] Comparative Example 1
[0055] (1) Weigh 90 parts of PP, 10 parts of commercially available diabase fiber, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;
[0056] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.
[0057] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0058] The PP composite materials prepared in the above Example 1 and Comparative Example 1 were made into strips by injection molding and tested. The test data are as follows:
[0059]
[0060] In general, the mechanical properties of Example 1 are better than those of Comparative Example 1.
[0061] Preparation Example 2
[0062] (1) Weigh 200 g of sodium dithiosuccinate, 600 g of ethanol, 400 g of diabase fiber, and 1.1 kg of deionized water, add them into a reaction vessel, and stir and react at 60° C. for 12 h to obtain solution A;
[0063] (2) Filtering solution A, washing it, and drying it in a vacuum oven at 80° C. for 5 h to obtain dithiol-modified diabase fiber B;
[0064] (3) Weigh 400 g of dithiol-modified diabase fiber B, 160 g of poly(methacrylate glycidyl) ester, 3 g of initiator ammonium persulfate, 4 g of surfactant sodium dodecylbenzene sulfonate, and 900 g of deionized water, place them in a reaction vessel, react at 40° C. for 16 h, filter, wash, and dry to obtain poly(methacrylate glycidyl) ester-coated modified diabase fiber M2.
[0065] Example 2
[0066] (1) Weigh 110 parts of PBT, 16 parts of modified diabase fiber M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0067] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.
[0068] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0069] Comparative Example 2
[0070] (1) Weigh 110 parts of PBT, 16 parts of commercially available diabase fiber, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0071] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.
[0072] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0073] The PBT composite materials prepared in the above Example 2 and Comparative Example 2 were made into test strips by injection molding machine, and the test data are as follows:
[0074]
[0075] In general, the mechanical properties of Example 2 are better than those of Comparative Example 2.
[0076] Preparation Example 3
[0077] (1) Weigh 180 g of sodium dimercaptosuccinate, 550 g of ethanol, 350 g of diabase fiber, and 1.0 kg of deionized water, add them to a reaction vessel, and stir at 50° C. for 10 h to obtain solution A;
[0078] (2) Filtering solution A, washing it, and drying it in a vacuum oven at 70° C. for 4 h to obtain dithiol-modified diabase fiber B;
[0079] (3) Weigh 350 g of dithiol-modified diabase fiber B, 130 g of glycidyl methacrylate, 2 g of initiator ammonium persulfate, 3 g of surfactant sodium dodecylbenzene sulfonate, and 800 g of deionized water, place them in a reaction vessel, react at 35° C. for 14 h, filter, wash, and dry to obtain modified diabase fiber M3 coated with polyglycidyl methacrylate.
[0080] Example 3
[0081] (1) Weigh 100 parts of PE, 13 parts of modified diabase fiber M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;
[0082] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.
[0083] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0084] Comparative Example 3
[0085] (1) Weigh 100 parts of PE, 13 parts of the dithiol-modified diabase fiber B prepared in step (2) of Example 3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;
[0086] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D3.
[0087] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0088] The PE composite materials prepared in the above Example 3 and Comparative Example 3 were made into test strips by injection molding machine, and the test data are as follows:
[0089]
[0090] In general, the mechanical properties of Example 3 are better than those of Comparative Example 3, which indicates that the modified diabase fiber-modified PE prepared in the present application has better physical properties than the dithiol-modified diabase fiber-modified PE.
[0091] Preparation Example 4
[0092] (1) Weigh 185 g of sodium dimercaptosuccinate, 585 g of ethanol, 375 g of diabase fiber, and 1.05 kg of deionized water, add them to a reaction vessel, and stir at 58° C. for 11 h to obtain solution A;
[0093] (2) Filtering solution A, washing it, and drying it in a vacuum oven at 75° C. for 4 h to obtain dithiol-modified diabase fiber B;
[0094] (3) Weigh 365 g of dithiol-modified diabase fiber B, 155 g of glycidyl methacrylate, 1.5 g of initiator ammonium persulfate, 2.5 g of surfactant sodium dodecylbenzene sulfonate, and 885 g of deionized water, place them in a reaction vessel, react at 38° C. for 12 h, filter, wash, and dry to obtain modified diabase fiber M4 coated with polyglycidyl methacrylate.
[0095] Example 4
[0096] (1) Weigh 85 parts of PA6, 14 parts of modified diabase fiber M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0097] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.
[0098] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0099] Comparative Example 4
[0100] (1) Weigh 85 parts of PA6, 14 parts of commercially available diabase fiber, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0101] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D4.
[0102] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0103] The PA6 composite materials prepared in the above Example 4 and Comparative Example 4 were made into strips by injection molding and tested. The test data are shown in the following table:
[0104]
[0105] In general, the mechanical properties of Example 4 are better than those of Comparative Example 4.
[0106] Preparation Example 5
[0107] (1) Weigh 195 g of sodium dithiosulfide succinate, 565 g of ethanol, 375 g of diabase fiber, and 945 g of deionized water, add them into a reaction vessel, and stir and react at 45° C. for 9 h to obtain solution A;
[0108] (2) Filtering solution A, washing it, and drying it in a vacuum oven at 75° C. for 4 h to obtain dithiol-modified diabase fiber B;
[0109] (3) Weigh 315 g of dithiol-modified diabase fiber B, 155 g of glycidyl methacrylate, 2.8 g of initiator ammonium persulfate, 3.6 g of surfactant sodium dodecylbenzene sulfonate, and 888 g of deionized water, place them in a reaction vessel, react at 31° C. for 15 h, filter, wash, and dry to obtain modified diabase fiber M5 coated with polyglycidyl methacrylate.
[0110] Example 5
[0111] (1) Weigh 95 parts of PET, 14 parts of modified diabase fiber M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;
[0112] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material P5.
[0113] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.
[0114] Comparative Example 5
[0115] (1) Weigh 95 parts of PET, 14 parts of commercially available diabase fiber, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;
[0116] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material D5.
[0117] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.
[0118] The PET composite materials prepared in the above Example 5 and Comparative Example 5 were made into strips by injection molding and tested. The test data are shown in the following table:
[0119]
[0120] In general, the mechanical properties of Example 5 are better than those of Comparative Example 5.
[0121] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent mechanical properties and can expand the application field of the thermoplastic resin composite material.
[0122] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0123] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A thermoplastic resin composite material with excellent mechanical properties, characterized in that: It is composed of the following components by weight: Thermoplastic resin 90-110 parts Modified diabase fiber 10-16 parts Antioxidant 0.1-0.5 parts The modified diabase fiber is dithiol-modified diabase fiber coated with poly(glycidyl methacrylate).
2. The thermoplastic resin composite material according to claim 1, characterized in that: The preparation method of the modified diabase fiber comprises the following steps: (1) adding sodium dithiosulfide succinate, ethanol and diabase fiber into deionized water and stirring for reaction; then filtering, washing and drying to obtain dithiosulfide-modified diabase fiber; (2) adding dithiol-modified diabase fiber, glycidyl methacrylate, an initiator, and a surfactant into deionized water for reaction, filtering, washing, and drying to obtain poly(glycidyl methacrylate)-coated dithiol-modified diabase fiber.
3. The thermoplastic resin composite material according to claim 2, characterized in that: The mass ratio of sodium dimercaptosuccinate, ethanol and diabase fiber in step (1) is (16-20): (50-60): (30-40).
4. The thermoplastic resin composite material according to claim 2, characterized in that: The stirring reaction in step (1) is carried out at a temperature of 40-60° C. and for a time of 8-12 h; The reaction temperature in step (2) is 30-40°C and the reaction time is 12-16h.
5. The thermoplastic resin composite material according to claim 2, characterized in that: The mass ratio of the dithiol-modified diabase fiber, glycidyl methacrylate, initiator, and surfactant in step (2) is (30-40): (10-16): (0.1-0.3): (0.2-0.4).
6. The thermoplastic resin composite material according to claim 2, characterized in that: The initiator in step (2) is ammonium persulfate, sodium persulfate, potassium persulfate or diisopropyl peroxydicarbonate.
7. The thermoplastic resin composite material according to claim 2, characterized in that: The surfactant in step (2) is sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate or nonylphenol polyoxyethylene ether.
8. The thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene or a mixture of several thereof.
9. The thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin is one of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate and polyamide 6.
10. The method for preparing a thermoplastic resin composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh 90-110 parts of thermoplastic resin, 10-16 parts of modified diabase fiber, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture; (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.